The effect of financial compensation on employee performance at pt. Bank btpn sungguminasa branch, gowa district - Putra, Eka Pradila (Indonesia Accounting Research Journal, 2023)
Financial compensation is one of the factors that can affect the level of employee performance. Compensation is an additional base salary that is not expected by employees, but only a part of it can be given only if they have certain achievements or certain skills and are not profitable if asked to complete it as soon as possible, such as reports or receipts that must be reported. This research was conducted using a simple linear regression analysis tool, f-test and t-test to analyze the closeness of a variable relationship. The purpose of this study was to determine the effect of financial compensation on employee performance at pt. bank btpn branch sungguminasa gowa district.